Stochastic dynamic analysis of composite plate with random temperature increment. (15th October 2019) - Chandra, S.; Sepahvand, K.; Matsagar, V.A.; Marburg, S.
Abstract: During the service life, laminated composites may be subject to some random thermal environment. Quantification of the uncertainty in static and dynamic response of the composites under such condition is still a challenging issue. This work presents a stochastic dynamic response analysis of a graphite-epoxy composite plate using generalized polynomial chaos (gPC) expansion due to random mean temperature increment. A stochastic finite element method (SFEM) based on the first-order shear deformation theory (FSDT) is used to describe the free and forced vibration response of the graphite-epoxy composite plate under a uniform distribution of the temperature throughout the plate. Newmark's time integration scheme is used to predict the time-dependent displacement response under dynamic loading. The collocation-based non-intrusive gPC expansion method is used for stochastic dynamic analysis of the graphite-epoxy composite plate. The increment in the temperature is considered as an uncertain parameter and presented by the truncated gPC expansion. The stochastic system response of the plate is projected to the deterministic solver by using the stochastic Galerkin method. The statistical response of eigen frequencies and dynamic displacements of the composite plate at incremental random mean temperature are investigated, and are compared with the results of the Monte Carlo simulation. The numerical studies show a reduction in amplitude of the dynamic mean displacements with the increment in the time and it increases with the increment in the random mean temperature. The characteristics of loading have also significantly influenced the uncertainty in the time-dependent displacement response.